Comparison Between Contract–Relax Stretching and Antagonist Contract–Relax Stretching on Gastrocnemius Medialis Passive Properties - Fukaya, Taizan; Konrad, Andreas; Sato, Shigeru; Kiyono, Ryosuke; Yahata, Kaoru; Yasaka, Koki; Onuma, Remi; Yoshida, Riku; Nakamura, Masatoshi (Frontiers in Physiology, 2022)
Antagonist contract–relax stretching and contract–relax stretching are commonly used in sports practice and rehabilitation settings. To date, no study has compared these modalities regarding muscle stiffness and stretch tolerance. This study aimed to investigate the effects of contract–relax and antagonist contract–relax stretching on dorsiflexion range of motion (ROM), stretch tolerance, and shear elastic modulus. Forty healthy participants (24 men and 16 women) took part in the study. Participants were randomly assigned to perform either contract–relax stretching or antagonist contract–relax stretching for 2 min. Outcomes were assessed on ROM, stretch tolerance, and shear elastic modulus before and after stretching. The ROM and stretch tolerance significantly increased after both contract–relax stretching (+5.4 ± 5.8 °, p < 0.05 ; +3.5 ± 8.0 Nm, p < 0.05) and antagonist contract–relax stretching (+6.1 ± 4.9 °, p < 0.05; +4.2 ± 6.4 Nm, p < 0.05); however, no significant difference was found between the two groups. Alternatively, the shear elastic modulus significantly decreased after both contract–relax (−31.1 ± 22.6 kPa, p < 0.05) and antagonist contract–relax stretching (−11.1 ± 22.3 kPa, p < 0.05); however, contract–relax stretching (−41.9% ± 19.6%) was more effective than antagonist contract–relax stretching (−12.5% ± 61.6%). The results of this study suggest that contract–relax stretching instead of antagonist contract–relax stretching should be conducted to decrease muscle stiffness. However, either contract–relax or antagonist contract–relax stretching can increase ROM.